Confirmation of Hemidactylus brookii Gray, 1845 from Borneo - Das, Indraneil; Sukumaran, Jeet
Hemidactylus brookii was described by Gray (1845) from collections made by British naval officer, Captain Edward Belcher (1799–1877) and the Earl of Derby, presumably the 14th Earl, Edward Geoffrey Smith Stanley (1799–1868). Collection locations are recorded as “Borneo” and “Australia” respectively. The three syntypes (BMNH 1947.3.6.47–49) have the type locality apparently restricted independently to “Borneo” by Smith, 1935: 89 and Pope, 1935: 460. The species is named for Sir James Brooke (1803–1868), who was known as the “First Rajah of Sarawak” (1842–1867). He was formerly Governor of Sarawak from 1841, and Governor of Labuan and Consul-General to the Sultan of Brunei from 1846